Підходи до забезпечення дотримання міжнародних договорів про охорону навколишнього середовища: між сприянням та примусом - Астанкевич, Юлія Ігорівна; Астанкевич, Ю. І.; Astankevych, Yuliia I.; Підгородинська, Юлія Ігорівна; Підгородинська, Ю. І.; Pidhorodynska, Yuliia I. (Одеса : Фенікс, 2022)
У статті розглянуто підходи до забезпечення дотримання міжнародних договорів про охорону навколишнього середовища. Визначено, що у міжнародному праві існують два основні підходи до забезпечення дотримання договорів та зобов’язань, що витікають з них: фасилітативний та примусовий, яким відповідають неконфронтаційні та конфронтаційні засоби реагування на порушення. У міжнародному праві навколишнього середовища зроблено акцент на підході сприяння дотриманню. Разом з тим, низці договорів властиві також конфронтаційні заходи. Авторка наголошує на необхідності поєднання двох підходів у розробленні процедури забезпечення дотримання міжнародних природоохоронних договорів із урахуванням об’єкта та цілей договору. Відповідне поєднання має підкріплюватися ефективними засобами та методами міжнародного контролю та проявлятися у повноваженнях відповідних органів контролю.

In the article approaches to ensuring compliance with international environmental agreements are considered. It is determined that in international law there are two main approaches to ensuring compliance with treaties and the obligations arising from them: facilitative or incentive and coercive, which correspond to non-confrontational and confrontational means of responding to violations. International environmental law gives preference to the facilitative approach since it shows itself more attractive for states that are often afraid of serious sanctions and other negative consequences of non-compliance with treaties. Moreover, the facilitative approach really helps developing states technically and financially to fulfill their obligations under multilateral environmental agreements. The most famous and successful example of them is the Montreal Protocol to the Vienna Convention for the Protection of the Ozone Layer of 1985. At the same time, a number of treaties are characterized by confrontational measures that are really necessary in the cases of voluntary non-compliance. The example of the latter is the Kyoto Protocol of 1997 to the United Nations Framework Convention on Climate Change of 1992, which has not proved itself efficient enough. The author emphasizes the need to combine two approaches in developing a procedure for ensuring compliance with international environmental agreements, taking into account the object and purposes of an agreement. On the one hand, it will give the parties more possibilities for voluntary compliance and, on the other hand, will stimulate them to do so by the risk of enforcement. The appropriate combination should be supported by effective means and methods of international verification and be manifested in the functions of compliance bodies. Hopefully the Paris Agreement of 2015 to the United Nations Framework Convention on Climate Change of 1992 will show itself a successful instance of such an approach.
Підгородинська Ю. І. Підходи до забезпечення дотримання міжнародних договорів про охорону навколишнього середовища: між сприянням та примусом / Ю. І. Підгородинська // Правова держава : науковий журнал. - № 47. – Одеса : Фенікс, 2022. – С. 91-97.
Keywords: міжнародні договори про охорону навколишнього середовища; підходи до забезпечення дотримання договорів; фасилітативний підхід; примусовий підхід; multilateral environmental agreements; approaches to ensuring compliance with agreements; facilitative approach; enforcement approach; Research Subject Categories::LAW/JURISPRUDENCE